PERANCANGAN SISTEM INFORMASI PADA VIHARA METTA BERBASIS WEBSITE - Ronny Ronny (Jurnal Ilmu Komputer dan Sistem Informasi, 2013)
Vihara Metta is a monastery built from Sangha Theravada Indonesia (STI) which is located at North Palmerah Street Number 26, West Jakarta. Now the information dissemination activities performed at this temple is still traditional, still a lot of obstacles contained in the manual system. Therefore the Vihara Metta want to implement web-based information system with a solution in the delivery of information to the people. The process of making this application programs using a waterfall methodology comprising the steps of planning, analysis, design, and implementation. Key wordsVihara Metta, information system, website, waterfall